2020
DOI: 10.1177/0894439320971233
|View full text |Cite
|
Sign up to set email alerts
|

Completion Conditions and Response Behavior in Smartphone Surveys: A Prediction Approach Using Acceleration Data

Abstract: This study utilizes acceleration data from smartphone sensors to predict motion conditions of smartphone respondents. Specifically, we predict whether respondents are moving or nonmoving on a survey page level to learn about distractions and the situational conditions under which respondents complete smartphone surveys. The predicted motion conditions allow us to (1) estimate the proportion of smartphone respondents who are moving during survey completion and (2) compare the response behavior of moving and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…For instance, GPS data provide information about respondents' geolocation and, thus, they can be used to infer the environmental setting (Kelly et al 2013;Struminskaya et al 2020). Similarly, acceleration data can help to provide information about the different motion conditions of smartphone respondents, such as standing or walking, during survey completion (Kern et al 2020). However, utilizing these potentials of mobile devices will require researchers to overcome device effects on consent behavior that have been reported by prior research (Wenz et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, GPS data provide information about respondents' geolocation and, thus, they can be used to infer the environmental setting (Kelly et al 2013;Struminskaya et al 2020). Similarly, acceleration data can help to provide information about the different motion conditions of smartphone respondents, such as standing or walking, during survey completion (Kern et al 2020). However, utilizing these potentials of mobile devices will require researchers to overcome device effects on consent behavior that have been reported by prior research (Wenz et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Data from acceleration and orientation sensors have also allowed researchers to infer participants' emotions [40,41]. Furthermore, Kern et al [42] showed that the accelerometer data recorded alongside the survey provided information about survey completion conditions (eg, whether a participant moved while taking the survey).…”
Section: This Study: Concurrent Sensingmentioning
confidence: 99%
“…Consequently, a very poor-performing model might simply originate from a participant's irregular behavior when filling out the questionnaire. However, contrary to the same issues with self-report data, combining sensors with pretrained classification algorithms might be fruitful for determining participants' activity levels for each measurement and informing the models beyond the aggregated features [25,42].…”
mentioning
confidence: 99%